Memorable error of Descartes: Leibniz Criticism of the Cartesian mechanics - Beltrán Ulate, Esteban Josué (2015)
This article aims to show a condensed overcoming the Cartesian thesis by GW Leibniz. Pre-established harmony - with the aim of providing a panorama, the origin of the Leibniz-Descartes about mechanics, it has its basis in contrast ocasionalism tension occurs. To accomplish this task, an approach to Leibniz's conception regarding the memorable mistake of Descartes is provided, then proceeds to the refutation of perpetual mechanical movement, according to the elucidation of the main confutations is finalizes specifying notion of dynamics and strength.